Szanse i bariery w funkcjonowaniu i rozwoju sektora MSP na obszarach wiejskich - Chądrzyński, Mariusz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2003)
The paper reviews some problems concerned with opportunities and threats attributed to the development process in the sector of small and medium sized enterprises located in rural areas. In the study, the following questions have been discussed: 1) the prospects for and trends in economic activities of small and medium sized enterprises in agri-food sector; 2) the external and internal environments which would limit business activities pursued by SME in rural regions.